Self-Compassion Dan Online-Fear Of Missing Out Pada Pengguna Instagram - Rahmania, Farra Anisa; Rahmayanti, Fitria Dian (Batanang : Jurnal Psikologi, 2023)
Self-compassion or self-compassion is a condition when someone loves and is kind to themselves. Self-compassion is often associated with individual behavior in accessing social media today. One interesting condition to study is the online fear of missing out Therefore, this research aims to determine the influence and correlation of self-compassion on online fear of missing out, especially among social media users. The participants in this research were 82 people who actively used Instagram. The scales used in this research are the Self-Compassion Scale (SCS) and the Online Fear of Missing Out (ON-FoMO) Scale. The data analysis used in this research is linear regression and correlation analysis. Based on the research results, it was found that there is a role of self-compassion of 8.4% in influencing online fear of missing out and there is also a negative correlation that occurs in these two variables. The correlation results show that the higher the self-compassion, the lower the participant's fear of missing out.Keywords: Self-Compassion, Online Fear of Missing Out, Social Media, Instagram